2017
DOI: 10.1111/tbed.12771
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the origins of genotype VIIh Newcastle disease in southern Africa

Abstract: It is widely accepted that Newcastle disease is endemic in most African countries, but little attention has been afforded to establishing the sources and frequency of the introductions of exotic strains. Newcastle disease outbreaks have a high cost in Africa, particularly on rural livelihoods. Genotype VIIh emerged in South-East Asia and has since caused serious outbreaks in poultry in Malaysia, Indonesia, southern China, Vietnam and Cambodia. Genotype VIIh reached the African continent in 2011, with the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 16 publications
(31 reference statements)
2
27
0
Order By: Relevance
“…The highest homology of this isolate is to a strain from Mozambique isolated in 2011 (KX231366) [24], sharing 97.87% nucleotide identity. It shares lower identities with sequences from South Africa and Mozambique [24,25], with nucleotide identities ranging from 95.21 to 97.7%. The subgenotype VII.2 identities of the isolates displayed in Figure 4 are in Table S2.…”
Section: Genotype VII Isolatementioning
confidence: 94%
“…The highest homology of this isolate is to a strain from Mozambique isolated in 2011 (KX231366) [24], sharing 97.87% nucleotide identity. It shares lower identities with sequences from South Africa and Mozambique [24,25], with nucleotide identities ranging from 95.21 to 97.7%. The subgenotype VII.2 identities of the isolates displayed in Figure 4 are in Table S2.…”
Section: Genotype VII Isolatementioning
confidence: 94%
“…As of 2019, at least 20 genotypes of NDV in class II and one in class I have been identified, and this number has been increasing [5]. Epidemiology reports have suggested that emerging strains exhibiting antigenic variations may be responsible for recent ND outbreaks in Africa and Asia [1,20]. These facts suggest that the conventional vaccine is insufficient for long-term control of ND.…”
Section: Introductionmentioning
confidence: 99%
“…Backyard flocks are implicated in maintaining enzootics of two critically important RNA viruses around the globe, NDV and HPAIV (237,(248)(249)(250)(251)(252)(253)(254)(255). This is largely due to essential differences in the biosecurity of backyard flocks and commercial flocks (238,256).…”
Section: Backyard Chickens and Biosecuritymentioning
confidence: 99%